Experimental Study on the Lubricated Oil Film Pressure of the Connecting-Rod Big End Bearing in the Experimental Device - Pham, Trung Thien; Tran, Thi Thanh Hai; Luu, Trong Thuan; Pham, Duc Minh (Old Journal, 2020)
This paper presents the experimental study of the lubricating oil film pressure of the connecting-rod big end bearing in the special device for the lubricating condition of the connecting-rod big end bearing. A connecting-rod model of photoelastic material is subjected to simulated load as in an engine. The oil film pressure is measured at different positions in the circumferential direction and the mid-section in length by a pressure sensor located on the shaft. The measured results show that the oil film pressure corresponds to the load acting on the connecting-rod. At the position 0° of the bearing, the oil film pressure reaches a maximum value around the 360° of crank angle, the zone of the explosion, and the oil pressure is at minimum at 720° (0°) angle of the crankshaft, corresponding to the minimum load zone to the connecting-rod. In the opposite position, at the 180° of the housing bearing, the oil film pressure is at minimum when an explosion occurs and is at maximum in the neighborhoods of 0° of the crank angle. At the other position of the connecting-rod, the oil film pressure is also corresponding to the load acting on the connecting-rod. The maximum value of oil film pressure decreases when the rotational speed of the crankshaft increases, the minimum pressure of the oil film slightly varies.